A Phase 1, Open-Label Assessment of a Dengue Virus-1 Live Virus Human Challenge Strain. (23rd June 2020) - Endy, Timothy P; Wang, Dongliang; Polhemus, Mark E; Jarman, Richard G; Jasper, Louis E; Gromowski, Greg; Lin, Leyi; De La Barra, Rafael A; Friberg, Heather; Currier, Jeffrey R; Abbott, Mark; Ware, Lisa; et al.
Abstract: Background: Dengue human infection models (DHIM) have been used as a safe means to test the viability of prophylaxis and therapeutics. Methods: A phase 1 study of 12 healthy adult volunteers using a challenge virus, DENV-1-LVHC strain 45AZ5, was performed. A dose escalating design was used to determine the safety and performance profile of the challenge virus. Subjects were evaluated extensively until 28 days and then out to 6 months. Results: Twelve subjects received the challenge virus: 6 with 0.5 mL of 6.5 × 10 3 plaque-forming units (PFU)/mL (low-dose group) and 6 with 0.5 mL of 6.5 × 10 4 PFU/mL (mid-dose group). All except 1 in the low-dose group developed detectable viremia. For all subjects the mean incubation period was 5.9 days (range 5–9 days) and mean time of viremia was 6.8 days (range 3–9 days). Mean peak for all subjects was 1.6 × 10 7 genome equivalents (GE)/mL (range 4.6 × 10 3 to 5 × 10 7 GE/mL). There were no serious adverse events or long-term safety signals noted. Conclusions: We conclude that DENV-1-LVHC was well-tolerated, resulted in an uncomplicated dengue illness, and may be a suitable DHIM for therapeutic and prophylactic product testing. Clinical Trials Registration: NCT02372175. Abstract : This nonrandomized trial in 12 healthy adults demonstrated that the DENV-1-LVHC challenge virus can safely induce an uncomplicated dengue illness.